At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
you must be missing some imformation... solve for a variable or what? we cannot solve with just that information given
there is no step to solve it
3 variables needs 3 equations..or is it 4 equations? its 3
maybe all 3 together? 1) 4x+6y-8z=1 2) -6x-9y+12z=0 3) x-2y-2z=3
I still need help as simple as possible to solve it, I'm not good at math and don't remem ber how please
first thing you need to do, is use the three equations to solve for a certain value of eachother, this is done by solving for a variable, then substituting
i would start with number 3, we can say that x-2y-2z=3 can be rewritten as x=3+2y+2z (moved em all over to make x alone
put it in a matrix calculator =p
so now you have what x is, you can then put that in for the other equations: 1)4(3+2y+2z)+6y-8z=1 2) -6(3+2y+2z)-9y+12z=0
... matricies would be easier, if you know how to do them?
I don't know, I haven't attempted to do this kind of math in over 15 years
the concept of matrices is a bit intuitive, if you want a shortcut to just the answer, a calculator would do it, if you need to know how to get it then ill continue algebraically
how do you know what x is when y and z are still unknowns?
please, if you don't mind
we dont technically know x, but we know how to phrase x in terms of y and z, this way we can put that into the other equations as i did here: 1) 4(3+2y+2z)+6y-8z=1 2) -6(3+2y+2z)-9y+12z=0
see how i first figured out (with equation 3) that x = 3+2y+2z... then put that new equation in for x in the other two equations? this way we no longer have three variables, we have two!
Oh okay I understand how you came up with 1 and 2
the goal is to solve for only one variable at a time, then find the other two after that
x =3+2y+2z 4(3+2y+2z) +6y-8z =1 --> 12+8y+8z+6y-8z=1 --> 14y= -11 --> y = -11/14 x =3+2y+2z --> x= 3+2(-11/14)+2z --> x= (3-11/7)+2z x= (10/7)+2z -6x-9y+12z=0---> -6(10/7)+2z-9(-11/14)+12z=0 ----> -60/7 + 99/14 +14z=0 -----> (-120+99)/14 +14z=0 -------> z = (21/14)/14 z= ........ u got y and z, and plug in to x =3+2y+2z, u get x
^there ya go haha
You are awesome Ty
ummm...I need help again, how does 12+8y+8z+6y-8z=1 become 14y=-11? I understand that when you multiple a positive with a negative it become positive, and I understand that 8z-8z cancels each other out, but then wouldn't it become 12+14y=1?
OOOOOH nm, I get it, 12+14y=1 becomes 14y=1-12
how does 3+2(-11/14) become 3-11/7?
14:2 = 7 ---> 3 + - 11/7 ---> 3-11/7
I'm sorry, I still don't understand how you come up with that. why does 2 do something with 14 and not -11?
2(-11/14)= -22/14 = 11/7, if u want it stay -22/14 that is ok